Faktor Pencetus Dan Faktor Risiko Rekurensi Herpes Simpleks Genitalis Dan Orolabialis - Donis, Ghefira Sonia; Hidayati, Afif Nurul; Machin, Abdullah; Alinda , Medhi Denisa (Syntax Corporation, 2025)
Herpes simplex is a sexually transmitted disease caused by the herpes simplex virus (VHS). Patients who have been infected with herpes simplex are susceptible to recurrence. So this research explains the trigger factors and recurrence of herpes simplex virus genitalis and orobialis. This research method is a retrospective study using medical records of herpes simplex patients. The research sample is inpatients diagnosed with herpes simplex according to the inclusion and exclusion criteria using total sampling technique. The number of samples for this study was 30 patients with herpes simplex virus. The independent variables of this research are UV rays, psychological stress, immunosuppression, and physical trauma. The dependent variable of this study is the trigger factor and recurrence of herpes simplex virus. Data analysis used the sperm rho statistical test to determine the correlation between variables. The statistical test results did not show a p value for exposure to UV light because there were no respondents who had a trigger factor in the form of UV light, p=0.000 and a correlation coefficient of 0.910 for psychological stress, p=0.001 and a correlation coefficient of 0.658 for immunosuppression, there was no p value because there was no there were respondents who had factors that trigger menstruation, p= 0.000 and a correlation coefficient of 0.979 for physical trauma against factors that trigger herpes simplex virus, there was no p value for cold weather trigger factors because no respondents experienced cold weather trigger factors. There is p = 0.053 and coefficient correlation 0.595 on the recurrence factor of UV exposure, p = 0.006 and coefficient correlation 0.769 on psychological stress, p = 0.022 and coefficient correlation 0.792 on immunosuppression, p = 0.009 and coefficient correlation 0.739 on menstruation, p = 0.000 and The correlation coefficient was 0.911 for physical trauma, and there was no p value for the cold weather factor because no respondents experienced cold weather recurrence factors. The conclusion is that there is no relationship between UV rays and menstruation as a trigger factor for herpes simplex, there is a relationship between psychological stress, immunosuppression and physical trauma to the trigger factors, there is a relationship between exposure to UV rays, psychological stress, immunosuppression, physical trauma to the recurrence factors of herpes simplex virus